A Multilevel Examination of Whether Child Welfare Worker Characteristics Predict the Substantiation Decision in Canada. Issue 5 (March 2023) - Lwin, Kristen; Fallon, Barbara; Filippelli, Joanne; Trocmé, Nico
The decision to substantiate a report of child maltreatment represents a key decision point in the child welfare service decision-making continuum. This decision has various potential implications for children and their families, which may include more intensive child welfare involvement or the cessation of services. The substantiation decision is determined by whether there is enough evidence to suggest that maltreatment or the risk of maltreatment has occurred. To date, there has been minimal exploration of whether child welfare worker characteristics might influence this critical decision point. The Decision-Making Ecology would suggest that indeed, worker characteristics play a role in how they carry out their role. Given the importance of this decision point, this study uses secondary data to examine whether worker characteristics, such as education level and type, ethnoracial identity, caseload, and experience, predict substantiation in the Canadian child welfare context. Furthermore, this study utilizes multilevel modeling, a theoretically important and unique method of analyzing organizational data that considers differences in decisions among child welfare workers. The final model included 4, 327 children and 567 workers from across Canada. Several case level factors (e.g., child age and functioning, caregiver risk factors) predicted the substantiation decision. Furthermore, and most importantly for this study, worker characteristics significantly predicted their substantiation decision. Workers with fewer years of experience, those in an Ongoing Services role, and with a lower caseload substantiated significantly more often than those with more work experience, in another role, and with higher caseloads. Lastly, caseload and years of experience, and training and caseload both interacted to predict the substantiation decision. Implications for policy and practice and future research areas are discussed.